2020
DOI: 10.1186/s12955-020-01566-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non-cardiovascular comorbidities on the quality of life of patients with chronic heart failure: a scoping review

Abstract: Purpose To determine the impact of non-cardiovascular comorbidities on the health-related quality of life (HRQoL) of patients with chronic heart failure (CHF). Methods A scoping review of the scientific literature published between 2009 and 2019 was carried out. Observational studies which assessed the HRQoL of patients with CHF using validated questionnaires and its association with non-cardiovascular comorbidities were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 59 publications
2
22
0
2
Order By: Relevance
“…The characteristics presented here might constitute the basis for deeper research into the concepts, and shows a huge need for professional support. Comorbidities negatively impact the quality of life and disability in patients with chronic diseases [ 45 , 46 ]. The comprehensive management of patients with CVD should include the treatment of comorbidities that have been associated with a worse quality of life, with special emphasis on anxiety and depression disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics presented here might constitute the basis for deeper research into the concepts, and shows a huge need for professional support. Comorbidities negatively impact the quality of life and disability in patients with chronic diseases [ 45 , 46 ]. The comprehensive management of patients with CVD should include the treatment of comorbidities that have been associated with a worse quality of life, with special emphasis on anxiety and depression disorders.…”
Section: Discussionmentioning
confidence: 99%
“…7 Servei d' Atenció Primària Barcelonés Nord i Maresme, Gerència Territorial Metropolitana Nord, Institut Català de la Salut, Barcelona, Spain. 8 Centre d' Atenció Primària La Riera (Mataró 1), Institut Català de la Salut, Barcelona, Spain. 9 Department of Medicine, Faculty of Medicine, Universitat de Girona, Girona, Spain.…”
Section: Abbreviationsunclassified
“…In asymptomatic patients without cardiovascular risks, transfusion is rarely needed until Hb drops below 7-8 g/dl or haematocrit falls between 21 and 24%, although there are some clinical circumstances in which is not recommended to let Hb drop that low for an extended period, or the optimal transfusion strategy is unclear. For example, in patients with coronary artery disease, it has been found that a restrictive transfusion strategy (in most cases, with the limit at 9 mg/dl) is linked to a higher risk of experiencing another cardiac ischemic event, while a personalized, liberal transfusion strategy lowers that same risk [7][8][9][10][11], however, the observed results of a recent clinical trial suggests that there may be merit to a restrictive strategy [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations